Growth performance and meat characteristics of the first filial Awassi Rambouillet callipyge ram lambs - Khaleel I. Z. Jawasreh; A. H. Al-Amareen; P. Y. Aad (Veterinary World, 2019)
Aim: This study was designed to introduce the callipyge (CLPG) and 50% of Rambouillet sheep genes to improve meat quality and quantity of Awassi (AW) sheep.